The Influence of Emotional Intelligence, Work Motivation, and Organizational Justice on Employee Performance with Organizational Citizenship Behavior as a Mediating Variable - Lusiana, Lusiana; Indah Fajar Dini, Yuli (Jurnal Manajemen, 2024)
Employee performance is one of the crucial factors for the sustainability of a company. Therefore, this research aims to examine the influence of emotional intelligence, work motivation, and organizational justice on employee performance, with organizational citizenship behavior as its mediation. This study utilized a quantitative method by collecting data through the distribution of a questionnaire consisting of 32 statements to several employees working in electronic distribution companies in Batam City. The questionnaire distribution was conducted online using Google Forms. From the questionnaire distribution, a total of 350 responses were obtained and analyzed using SPSS and Smart PLS. The results of this study indicate that out of the ten proposed hypotheses, six hypotheses have a significant influence, while four hypotheses do not. The hypotheses with significant results are: (H2) work motivation has a significant influence on employee performance, (H3) emotional intelligence has a significant influence on employee performance, (H4) organizational justice has a significant influence on organizational citizenship behavior, (H5) work motivation has a significant influence on organizational citizenship behavior, (H7) organizational citizenship behavior has a significant influence on employee performance, and (H9) work motivation has a significant influence on employee performance with the mediation of organizational citizenship behavior. On the other hand, the remaining four hypotheses show non-significant results.